Förskollärares kommunikation med de yngsta barnen i förskolan: med fokus på kvalitativa skillnader i hur ett innehåll kommuniceras. - Agneta Jonsson (Nordisk Barnehageforskning, 2016)
The aim of this article is to describe and analyze how preschool teacher’s ways to communicate with the youngest children in preschool contributes to conditions for children's learning. Data has been gathered from four Swedish preschools where observations were conducted to study teachers' communication with 1-3 year old children. The results of the study showed qualitative differences in teachers’ communication about a content. One conclusion is that a broad repertoire of ways to communicate seems to favor conditions for children as actors to jointly expand the content in focus. Another conclusion is that the repertoire of children's actions and expressions made possible appears to be related to qualitative differences in teachers’ communication.